2003
DOI: 10.1124/jpet.103.049551
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric-Oxide Synthase Isoforms in Nitrous Oxide Antinociception in Mice

Abstract: Exposure of mice to the anesthetic gas N 2 O evokes a prominent antinociceptive effect that is sensitive to antagonism by nonselective nitric-oxide synthase (NOS) inhibitors. The present study was conducted to identify whether a specific NOS isoform is implicated in N 2 O antinociception in mice. In the abdominal constriction test, exposure of mice to 25, 50, and 70% N 2 O resulted in a concentration-dependent antinociceptive effect that persisted for up to 6 min following removal of the mice from the N 2 O at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Whereas eNOS-derived NO consistently shows a protective role in hypertension [36,37], there are, however, some inconsistencies in the literature regarding the role of nNOS- and iNOS-derived NO in BP regulation. For instance, several reports show decreased BP after nNOS inhibition [36,38,39], whereas others show the opposite [4042]. Likewise, some studies describe a role for iNOS in the pathogenesis of hypertension [37,43,44] even as other studies show protective effects [4547].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas eNOS-derived NO consistently shows a protective role in hypertension [36,37], there are, however, some inconsistencies in the literature regarding the role of nNOS- and iNOS-derived NO in BP regulation. For instance, several reports show decreased BP after nNOS inhibition [36,38,39], whereas others show the opposite [4042]. Likewise, some studies describe a role for iNOS in the pathogenesis of hypertension [37,43,44] even as other studies show protective effects [4547].…”
Section: Discussionmentioning
confidence: 99%
“…The neurochemical mediators through which inhaled N 2 O might increase peripheral blood flow could involve nitric oxide (NO), a potent vasodilator with an important role in blood flow distribution (69). A role for NO in N 2 Oaugmented heat dissipation seems plausible in part because Quock and colleagues (7,26,28) have implicated NO in other N 2 O effects, specifically its antinociceptive and anxiolytic effects. Additionally, because hypoxia-induced hypothermia is attenuated by microinjection of a NO synthesis inhibitor in the preoptic hypothalamus (65), it is possible that central as well as peripheral NO release could participate in mediating the hypothermic effect of N 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…NOS activity is apparently critical to the antinociceptive response to N 2 O since N 2 O-induced antinociception in rats and mice is blocked by pretreatment with any of a variety of NOS-inhibiting arginine analogs (McDonald et al, 1994;Ishikawa and Quock, 2003a) and also by pretreatment with an antisense oligodeoxynucleotide directed against the neuronal NOS enzyme (Li et al, 2004). Moreover, DBA/2 inbred mice that are poorly sensitive to N 2 O-induced antinociception failed to exhibit an increase in NOS enzyme activity during exposure to N 2 O when compared to N 2 O-sensitive C57BL/6 mice (Ishikawa and Quock, 2003b;Henry et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the antinociceptive effect of N 2 O is also antagonized by inhibition of nitric oxide (NO) production (McDonald et al, 1994;Ishikawa and Quock, 2003a;Li et al, 2004), implicating an involvement of NO in the drug effect as well. The present study was conducted to ascertain whether the opioid receptors and NO function that are involved in N 2 O-induced antinociception are co-localized in the periaqueductal gray (PAG) of the midbrain, which has been shown to be involved in N 2 O-induced antinociception (Zuniga et al, 1987;Hodges et al, 1994;Fang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%